Answer:
x=4
Explanation:
Simplifying
8x + -6 = 3x + 14
Reorder the terms:
-6 + 8x = 3x + 14
Reorder the terms:
-6 + 8x = 14 + 3x
Solving
-6 + 8x = 14 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
-6 + 8x + -3x = 14 + 3x + -3x
Combine like terms: 8x + -3x = 5x
-6 + 5x = 14 + 3x + -3x
Combine like terms: 3x + -3x = 0
-6 + 5x = 14 + 0
-6 + 5x = 14
Add '6' to each side of the equation.
-6 + 6 + 5x = 14 + 6
Combine like terms: -6 + 6 = 0
0 + 5x = 14 + 6
5x = 14 + 6
Combine like terms: 14 + 6 = 20
5x = 20
Divide each side by '5'.
x = 4
Simplifying
x=4
answer x=4